The Role of Mindfulness in Addressing Burnout among Healthcare Professionals: A Systematic Review - Indah Sari Liza Lubis (Attractive : Innovative Education Journal, 2024)
Those employed in the field of health are a profession that interacts directly with patients on a regular basis and therefore are exposed to significant stressors. The considerable number of responsibilities, the high complexity of the work, and the demands placed upon health workers make the health worker profession susceptible to stress and burnout. The objective of this study is to ascertain the impact of mindfulness-based interventions on mitigating burnout among healthcare professionals at Hospital "X" in Jogjakarta City. This study employs the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) and the Five Facet Mindfulness Questionnaire (FFMQ) as manipulation checks. This study employs an experimental methodology to investigate the impact of the independent variable, mindfulness-based stress reduction (MBSR), on the dependent variable, burnout. The findings indicate that a mindfulness-based intervention, specifically the MBSR method, has a notable effect on reducing burnout among health workers at Hospital "X."